ANALISIS NILAI RELIGIUSITAS DALAM NOVEL TUHAN, MAAF ENGKAU KUMADU KARYA AGUK IRAWAN MN - Irma Sendy Aristya (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2016)
This study aimed to describe the values of religiosity in the novel Tuhan, Maaf Engkau Kumadu by  Aguk Irawan MN. This type of research is qualitative. Metode yang used in this research is the method deslriptif. The results of this study are as follows: First, religious values associated with Qalb or liver (which has the pleasure principle) which is reflected from the main character is that Ridho is a young man who greatly admired her idol Nisa. He always thought of Nisa every second of it, it makes Ridho feel happy. Because kept thinking and shadowing Nisa through dreams regardless of his Lord. Second, Fuad is feeling the most in the so-called conscience, which serves as a store of memory. Fuad demonstrated by Ridho who underwent a drastic change in his life. Now he is getting misguided souls burning would love to Nisa that led to the injury because only love is unrequited. Third, the ego aspect demonstrated by Ridho when he was uniting between feelings of love and compassion through the pieces out as a form hubb (love) to Nisa. Selfishness is done the main character just thinking of the girl regardless of the people around him. And the fourth, aspects of behavior shown by Ridho as the main character is less normal and can not be in the logic of reason.  Keywords: value,  religiosity, novel